Hispania, A journal devoted to the teaching of Spanish and Portuguese, Los Angeles, University of Southern California, vol. 70, núms. 1, 2, 3 y 4 de 1987. - Villarreal Vásquez, Luis José (Thesavrvs, 2023)
Reseñas de revistas.